IMPLEMENTATION OF THE ASYIK MODEL IN IMPROVING TEACHERS' CREATIVE COMPETENCE IN TEACHING AT TKN DUREN SAWIT 02 - Wirastri Setyorini; Yulia Indrawati; Sri Endah Wahyuningsih; Sri Watini (Jurnal Scientia, 2022)
Educational efforts, especially in improving quality human resources who have high creativity and high independence, are very strategic in view of productive and creative learning models in these efforts to develop teachers' creative competence in the learning process. . In realizing the quality values ​​of each educational institution, efforts can be made through learning activities. Teachers have duties and roles in choosing and developing learning strategies that can provide learning experiences and develop students' potential by implementing an innovative and creative learning model. The teaching model that can be applied can be adopted from the ASYIK model at TKN Duren Sawit 02, taking into account the development of potential aspects that exist in children carried out with the principle of playing while learning, sing and move so that it can attract children's interest in learning, therefore efforts are needed that are able to facilitate children's growth and development in the form of fun according to the age, needs and interests of children. The role of the teacher is needed so that the child's potential is more focused and also help from parents so that what children do is fun